PENGEMBANGAN KERAJINAN SAAB MOTE DI DESA NAGASEPAHA - Kadek Doddy Purna Hendrawan; Ngurah Tedi Saniartha; Gusti Putu Eka Kusuma; Mertyani Sari Dewi (Pusat Riset dan Inovasi Nasional, 2022)
Problems in this aspect, namely, experiencing problems with the use of production tools that are still manual and less labor which causes the production process to be very long so that the income to produce handicraft products is very little. In the marketing aspect in this Saab Mote craftsman, the way to promote is only by word of mouth. From the marketing aspect, the scope of marketing is still very narrow. Judging from the small market place for saab mote craftsmen and the marketing reach that is still not maximized by only marketing it at home by relying on how many customers at least buy saab mote craft products and have not marketed them to traditional markets or other marketing places, this saab mote craft is only watched on one motive namely floral motifs that cause customer boredom because they only have one motive. The results in the field for saab mote craftsmen in general are to improve human resources in terms of mindset regarding the ebb and flow of market waves through increasing production and marketing aspects. By studying entrepreneurship, which is the ability to create something new and different, while someone who has the ability to create something that has never existed before, or it could be by creating something different from what exists.